(untitled) (Texas Journal of Medical Science, 2025)
Broncho-obstructive syndrome (BOS) is an inflammation of the bronchi, accompanied by severe swelling of the bronchi and the production of large amounts of mucus. This substance is difficult to expel, causing mucus to stagnate and create a favorable environment for bacteria. Bronchial obstruction is dangerous due to the development of respiratory failure and oxygen starvation, which is especially dangerous for small children.